THE EFFECT OF SERVICE QUALITY ON SATISFACTION AND LOYALTY VISITORS AT SENGKALING RECREATIONAL PARK - Ardik Praharjo (Manajemen Bisnis, 2020)
Loyalty is needed by the company because it will maintain business continuity. This study aims to determine the effect of service quality on the satisfaction and loyalty of visitors to the Sengkaling Recreational Park both directly and indirectly. The type of research used is explanatory research with a quantitative approach. Sample technique in this research using purposive sampling. The sample used is 112 visitors who have visited at least twice and over 18 years old. The data analysis technique used is descriptive research and using path analysis. The results of this study indicate that service quality has a significant effect on visitor satisfaction and loyalty at Sengkaling recreational park.